Analysis of the Implementation of the Orya Hydroelectric Power Plant's Island Defense Scheme in the Jayapura Power System - Wardiman; Yosef Lefaan; Oktavianus Kati; Joni (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
This study aims to determine whether the islanding-based defense scheme at the Orya hydropower plant can effectively maintain the stability of the Jayapura radial power system during major disturbances. The system was modeled and tested in DIgSILENT PowerFactory under several outage scenarios, with a focus on the separation of the Orya–Sentani–Skyline corridor. The simulation indicates that maintaining post-disturbance operation within the nominal frequency of around 50 Hz and voltage variation of ±5% requires shedding 19.89 MW of load from selected feeders. After the scheme is activated, the islanded Orya subsystem settles at approximately 50.15 Hz, while the remaining grid stabilizes near 50.0 Hz—both within regulatory limits. These findings suggest that a combined load-shedding and islanding strategy can reduce the risk of cascading failures in Jayapura and may offer a practical template for other radial systems with limited redundancy.